The degree of Availability of the Global mathematics standards in the Geometry axis in the mathematics books of (1 st - 4th) grades, from the point of view of female teachers in the Sultanate of Oman - Alriyami, Mohammed Nassir Saif (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the NCTM Global Mathematics Standards in the content of the geometry axis of mathematics books for grades (1-4) As well as revealing the availability of those standards in the content of the geometry axis of mathematics books for grades (1-4) from the point of view of female teachers in the Sultanate of Oman.The study used a descriptive method also used the questionnaire to collect data and information were applied to a sample of (114) female teachers.The results of the study reached a list of the NCTM global mathematics standards needed to be available in the the content of the geometry axis of mathematics books for grades (1-4), and it was judged and defined in (40) paragraphs , divided into four main axes: (Analysis of the properties of two- and three-dimensional geometric shapes, determination of positions using coordinate geometry and other representation systems, application of geometric transformations to analyze mathematical situations and the focus of using mental visualization to solve problems.). The study also revealed that the degree of availability of the NCTM International Mathematics Standards (for four axes) in the content of the geometry axis of mathematics books for grades (1-4) from the point of view of female teachers in the Sultanate of Oman, in general, was a medium degree. While the availability of the four axes separately came as follows (medium, few, medium and medium) respectively.
Keywords: NCTM International Mathematical Standards; geometry axis; mathematics books